4 minutes and 30 seconds go into 2 hours 26 times
119
Answer: 4(x + 9) = 3x − 8 − 5
Step-by-step explanation:
Hi, to answer this question we have to analyze the equation given:
4(x + 9) + 5 = 3x − 8
The subtraction property of equality states that if we subtract the same number from both sides of the equation, the equality remains.
So, if we subtract 5 from both sides:
4(x + 9) + 5-5 = 3x − 8 -5
4(x + 9) = 3x − 8 − 5
Feel free to ask for more if needed or if you did not understand something.
Y = x^2 + 10x - 171
y = (x - 9)(x + 19)
x - 9= 0 x + 19 = 0
x = 9 x = -19
Answer B covers all requirements... the factored form is
y= (x + 19)(x - 9)
and the zeros are -19 and 9